Co-Development of Diagnostic Vectors to Support Targeted Therapies and Theranostics: Essential Tools in Personalized Cancer Therapy - Nicolaides, Nicholas C.; O’Shannessy, Daniel J.; Albone, Earl; Grasso, Luigi (Frontiers in Oncology, 2014)
Novel technologies are being developed to improve patient therapy through the identification of targets and surrogate molecular signatures that can help direct appropriate treatment regimens for efficacy and drug safety. This is particularly the case in oncology whereby patient tumor and biofluids are routinely isolated and analyzed for genetic, immunohistochemical and/or soluble markers to determine if a predictive biomarker signature exists as a means for selecting optimal treatment. Improvements in diagnostics that can prescreen predictive response biomarker profiles will continue to optimize the ability to enhance patient therapy via molecularly defined disease-specific treatment. A goal for drug developers is to identify and implement new strategies that can rapidly enable the development of beneficial disease-specific therapies for broad, patient-specific targeting without the need of tedious predictive biomarker discovery and validation efforts, currently a bottleneck for development timelines. Here we discuss the use of co-developing diagnostic-targeting vectors to identify patients whose malignant tissue can specifically uptake a drug linked vector prior to treatment. Using this system, a patient can be predetermined in real time as to whether or not their tumor(s) can uptake a drug-linked diagnostic vector, thus inferring the uptake of a similar vector linked to an anti-cancer agent. If tumor-specific uptake is observed, then the patient may be suitable for drug-linked vector therapy and have a higher likelihood of clinical benefit while patients with no tumor uptake should consider other therapeutic options. This approach offers complementary opportunities to rapidly develop broad tumor-specific agents for use in personalized medicine.